Excessive Electronic Screen Exposure and Headache in Teenagers - Mohsana Tariq, Khizra Asif, Hafiza Azka Khursheed, Zainab Khalid, Muqaddas Ashfaq, Afifa Maryam, Seerat Fatima, Nimra Aslam, Hira Masood, Mahnoor Mazhar Alvi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Headache represents the most common neurologic disorder in the general population including children and is increasingly being recognized as a major source of morbidity in youth related to missed school days and activities. Electronic screens are becoming increasingly important in the lives of preteens and teens. Objective: Study was conducted to find the relationship between electronic screen exposure and headaches in teenagers. Methods: This was a cross-sectional study. Data was collected 300 teenagers from district Mandi-bahu-Din. Convenient sampling was applied. Teenager aged between 12-19 years, physically and mentally healthy and both genders were selected to include in study. Person with history of head injury, hypertension and systemic disease-causing headache were excluded from study. data was collected through using 2 reliable questionnaires; Headache impact test-6 and Screen time survey questionnaire. Data was analyzed using statistical package for social sciences (SPSS) V 23. Descriptive statistics in form of frequency and percentages was presented. Bar and pie charts were plotted. To find association between screen time and headache Pearson correlation was applied. Results: There was significant (P=0.021) correlation between screen time and headache with coefficient of correlation r= 0.414.Excessive electronic screen exposure is negatively impacting the life of 46% (n=139) teenagers. Mean age of participants was 14.95±1.88. Mean and SD of screen time is 5.15±1.73. Mean and SD for headache is 54.9±4.93. There were 45% males and 55% female participants. Practical implication: Different types of electronic screen media have repeatedly been linked to impaired health; yet, how different uses of electronic media are linked to headache has received much less attention. Currently, the role of chronotype in these associations is understudied. To address these gaps, this study examined how different uses of screen media are linked to headache, and whether these associations were accounted for or differed across chronotype. Conclusion: It was concluded that screen time and headache have significant correlation with each other. Keywords: Headache, Screen Time, Electronic Screen Exposure.